Hunger Games : Sunrise on the Reaping - Book 5 - Collins, Suzanne (New York : Scholastic Press, 2025)
As the day dawns on the fiftieth annual Hunger Games, fear grips the districts of Panem. This year, in honor of the Quarter Quell, twice as many tributes will be taken from their homes. Back in District 12, Haymitch Abernathy is trying not to think too hard about his chances. All he cares about is making it through the day and being with the girl he loves. When Haymitchs name is called, he can feel all his dreams break. Hes torn from his family and his love, shuttled to the Capitol with the three other District 12 tributes: a young friend whos nearly a sister to him, a compulsive oddsmaker, and the most stuck-up girl in town. As the Games begin, Haymitch understands hes been set up to fail. But theres something in him that wants to fight... and have that fight reverberate far beyond the deadly arena. (Companion novel)
Keywords: Contests -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Dystopias -- Juvenile fiction; Contests -- Fiction; Insurgency -- Fiction; Survival -- Fiction; Young adult fiction; Dystopian fiction; Science fiction